Detection of LytA Genes in Streptococcus pneumoniae Isolated from sputum pneumonia patients - Mustika Sari Hutabarat; Firdaus Hamid; Irawaty Djaharuddin; Alfian Zainuddin; Rossana Agus; Muhammad Nassrum Massi (Biomedika, 2020)
Streptococcus pneumoniae (pneumococcus) is a Gram-positive facultative anaerobic bacterium that is a major cause of morbidity and mortality worldwide. But the lack of reporting of disease by this bacterium in Indonesia, one of the causes is because the diagnosis of pneumococcal infection is often clinically not typical and conventional methods which are still the standard gold method often give false-negative results. So the purpose of this study was to evaluate the performance of culture and molecular diagnostic methods using the Polymerase Chain Reaction (PCR) technique in detecting Streptococcus pneumoniae in sputum clinical samples using the Autolysin (LytA) gene which is a virulence factor of this bacterium. 57 isolates from 60 samples were confirmed as Streptococcus sp through microscopic identification, culture, and biochemical tests. Then the sensitivity test with an optochin test of 9 (9%) compared the results descriptively with the PCR technique using the Autolysin A (LytA) gene which was obtained more sensitive by 15 (25%).